The The Influence of Work Discipline, Organizational Culture and Competence on Employee Performance: (Study on Bukit Asam Tbk Company. Kertapati Pier Unit, South Sumatera) - Agusria, Lesi; Fitantina, Fitantina; Kholilah, Kholilah; Permana, Arraditya (International Journal of Business, Management and Economics, 2022)
This research discusses the influence of work discipline, organizational culture and competence on employee performance in Bukit Asam, Tbk Company, Kertapati Pier Unit, South Sumatera. This type of research is associative. The population in this study were all employees of PT. Bukit Asam Tbk. Kertapati Jetty Unit, South Sumatra, totalling 113 employees, and the samples taken in this study were 84 respondents with the sampling technique of proportionate stratified random sampling. The analytical method used is qualitative, which is then quantified. The data analysis technique used in this research is multiple linear regression analysis, F test, t-test and coefficient of Determination. The data used in this study is primary data collected through the Kuesioner method. Data analysis techniques are performed with multiple linear regression. The Results showed that (1). there is a significant influence on work discipline (X1), organizational culture (X2) and competence (X3) on employee performance (Y) of PT. Both simultaneously and partially, Bukit Asam Tbk Company, Kertapati Pier Unit, South Sumatera. (2). The results of Multiple Linear Regression show that Work Discipline, Organizational Culture and Competence have a positive relationship direction for employee performance in Bukit Asam Tbk company, Kertapati pier unit, South Sumatera (3). The results of the coefficient of Determination of work discipline, organizational culture and competence can only contribute to changes that occur in employee performance with a significant contribution of 79.5%.